2020
DOI: 10.1101/gr.249045.119
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screening reveals genes essential for cell viability and resistance to abiotic and biotic stresses in Bombyx mori

Abstract: High-throughput genetic screens are powerful methods to interrogate gene function on a genome-wide scale and identify genes responsible to certain stresses. Here, we developed a piggyBac strategy to deliver pooled sgRNA libraries stably into cell lines. We used this strategy to conduct a screen based on genome-wide clustered regularly interspaced short palindromic repeat technology (CRISPR)-Cas9 in Bombyx mori cells. We first constructed a single guide RNA (sgRNA) library containing 94,000 sgRNAs, which target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 54 publications
(59 reference statements)
0
27
0
Order By: Relevance
“…Among them, the ABC transporter pathway has been identified in multiple proteome and transcriptome studies [ 9 , 40 ]. In previous studies, knockout of the V-ATPase subunit gene BMgn016795A of the ABC transporter pathway resulted in a significant decrease in proliferation of BmNPV in BmE cells [ 8 ]. The endosomal acidification mediated by this gene may play a role in the process of BmNPV entering cells, although the mechanism is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the ABC transporter pathway has been identified in multiple proteome and transcriptome studies [ 9 , 40 ]. In previous studies, knockout of the V-ATPase subunit gene BMgn016795A of the ABC transporter pathway resulted in a significant decrease in proliferation of BmNPV in BmE cells [ 8 ]. The endosomal acidification mediated by this gene may play a role in the process of BmNPV entering cells, although the mechanism is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Bombyx mori nucleopolyhedrovirus (BmNPV) baculovirus is a major pathogen of the silkworm and causes serious economic losses [ 6 , 7 ]. Genetics and molecular biology studies have generated antiviral strains and revealed immunological responses [ 8 , 9 , 10 , 11 , 12 ]. However, the resistance mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of resistance genes and analysis of silkworm antiviral mechanisms against BmNPV merit further investigation. In future experiments, we will screen for negative regulatory factors in the immune pathway using genome-wide CRISPR ( 114 ) and identify the host proteins that bind the virus by use of inhibitors. The target genes will be knocked out via gene editing to improve silkworm resistance.…”
Section: Future Directions Of Silkworm Antivirus Researchmentioning
confidence: 99%
“…castaneum and the silk moth Bombyx mori . We used the available RNA interference (RNAi) ( 24 ) and CRISPR ( 25 ) screen with defined lethality status as a control, while validating further predictions experimentally. Moreover, we aimed to fill the gap between human cell line screens and population studies, by integrating information from the model organisms to improve human essential gene assignments.…”
Section: Introductionmentioning
confidence: 97%